Hepatic Macrophage as a Key Player in Fatty Liver Disease - Xu, Liyun; Liu, Wen; Bai, Fuxiang; Xu, Yong; Liang, Xiaohong; Ma, Chunhong; Gao, Lifen (Frontiers in Immunology, 2021)
Non-alcoholic fatty liver disease (NAFLD), characterized by excessive inflammation and lipid deposition, is becoming one of the most prevalent liver metabolic diseases worldwide owing to the increasing global incidence of obesity. However, the underlying mechanisms of NAFLD are poorly understood. Accumulating evidence suggests that hepatic macrophages, specifically Kupffer cells (KCs), act as key players in the progression of NAFLD. Thus, it is essential to examine the current evidence of the roles of hepatic macrophages (both KCs and monocyte-derived macrophages). In this review, we primarily address heterogeneities and multiple patterns of hepatic macrophages participating in NAFLD pathogenesis, including Toll-like receptors (TLRs), NLRP3 inflammasome, lipotoxicity, glucotoxicity, metabolic reprogramming, interaction with surrounding cells in the liver, and iron poisoning. A better understanding of the diverse roles of hepatic macrophages in the development of NAFLD may provide a more specific and promising macrophage-targeting therapeutic strategy for inflammatory liver diseases.